The Urgency of Prototype Curriculum Based E-Book for Mathematics Learning for Vocational School Students - Budiarto, Lulus; Akhyar, Muhammad; Djono (Journal of Education Technology, 2022)
The development and learning paradigm is always followed by adjustments to the implementation of learning activities. Currently, a solution is being offered to improve the quality of learning through the implementation of kurikulum prototype. This study aims to see the potential and opportunities for product development of teaching materials based on E-Books for learning mathematics. This research belongs to the mixed methods approach. The research subjects consisted of teachers, and 42 students. While the data collected in the form of qualitative and quantitative data. Qualitative data were collected with technical observations, and interviews with the instruments, namely observations and interviews. Quantitative data were collected using a non-test technique, namely a questionnaire and followed by a questionnaire as an instrument. The research data will be analyzed descriptively with interactive analysis through data collection, data reduction, data presentation, and drawing conclusions. The results showed that during the implementation of learning, teachers had basically used ICT-based media which were limited to the type of presentation slides and the internet, student responses stated that they needed ICT-based teaching materials for learning mathematics (92.9%), total 90.5% of students also agrees with the development of ICT-based teaching materials in e-book format for learning mathematics, this is certainly an initiative and desire that must be realized in order to implement innovative learning. Thus, the results of this study can be used as a basis for developing an innovation through ICT-based teaching materials in e-book format to improve the learning process in vocational high schools.